The Effect of Sevoflurane Versus Total Intravenous Anesthesia on Intraocular Pressure in Patients Undergoing Coronary Artery Bypass Graft Surgery with Cardiopulmonary Bypass: A Prospective Observational Study - Zeynep Yasemin Tavsanoglu; Ali Sait Kavakli; Senay Canim Erdem; Arzu Karaveli; Ulku Arslan; Adnan Yalcinkaya; Ali Umit Yener; Berna Dogan (Medicina)
Background and Objectives: The aim of this study was to compare the effects of sevoflurane-based anesthesia and propofol-based total intravenous anesthesia (TIVA) on intraocular pressure (IOP) during coronary artery bypass graft surgery (CABG) with cardiopulmonary bypass (CPB). Materials and Methods: This prospective observational monocentric study included 68 patients scheduled for CABG with CPB, divided into two groups of propofol-based TIVA (Group P) and sevoflurane-based anesthesia (Group S). Intraocular pressure was measured and recorded at eight predefined time points using a tonometer: before anesthesia induction (T1), 10 min after induction (T2), immediately before the beginning of CPB (T3), 3 min after the beginning of CPB (T4), 3 min after cross-clamping (T5), 3 min after cross-clamp removal (T6), immediately before the weaning of CPB (T7), and at the end of the surgery (immediately after skin closure) (T8). The primary endpoint was to examine the effects of propofol-based TIVA and sevoflurane-based anesthesia methods on IOP during CABG operation. The secondary endpoints included a comparison of hemodynamic variables, blood gas values, and intensive care unit (ICU) and hospital stays. Results: Intraocular pressure values were similar for both groups at all time points. A statistically significant decrease was found in IOP in all measurements after induction compared to pre-induction values in both Group P and Group S (p < 0.05). Compared to IOP measured at 10 min after induction, no statistically significant difference was found at all subsequent time points in both groups. When the right and left IOP values were compared, no statistically significant difference was detected at all time points in both Group P and Group S. Conclusions: The results of the study indicated that propofol-based TIVA and sevoflurane-based anesthesia had similar effects on IOP in patients undergoing CABG with CPB.